Clinical associations of proinflammatory cytokines, oxidative biomarkers and vitamin D levels in systemic lupus erythematosus. (December 2017) - Willis, R; Smikle, M; DeCeulaer, K; Romay-Penabad, Z; Papalardo, E; Jajoria, P; Harper, B; Murthy, V; Petri, M; Gonzalez, E B
Background: The abnormal biological activity of cytokines plays an important role in the pathophysiology of both systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS). Several studies have highlighted the association of vitamin D and certain pro-inflammatory cytokines with disease activity in SLE. However, there are limited data on the association of vitamin D and antiphospholipid antibodies (aPL) with various proinflammatory biomarkers in these patients and their relative impact on clinical outcomes. Methods: The serum levels of several aPL, 25-hydroxy-vitamin D, pro-inflammatory cytokines including IFNα, IL-1β, IL-6, IL-8, IP10, sCD40L, TNFα and VEGF were measured in 312 SLE patients from the Jamaican ( n  = 45) and Hopkins ( n  = 267) lupus cohorts using commercial Milliplex and ELISA assays. Oxidized LDL/β2glycoprotein antigenic complexes (oxLβ2Ag) and their associated antibodies were also measured in the Jamaican cohort. Healthy controls for oxidative marker and cytokine testing were used. Results: Abnormally low vitamin D levels were present in 61.4% and 73.3% of Hopkins and Jamaican SLE patients, respectively. Median concentrations of IP10, TNFα, sCD40L and VEGF were elevated in both cohorts, oxLβ2Ag and IL-6 were elevated in the Jamaican cohort, and IFNα, IL-1β and IL-8 were the same or lower in both cohorts compared to controls. IP10 and VEGF were independent predictors of disease activity, aPL, IP10 and IL-6 were independent predictors of thrombosis and IL-8, and low vitamin D were independent predictors of pregnancy morbidity despite there being no association of vitamin D with pro-inflammatory cytokines. Conclusions: Our results indicate that aPL-mediated pro-inflammatory cytokine production is likely a major mechanism of thrombus development in SLE patients. We provide presumptive evidence of the role IL-8 and hypovitaminosis D play in obstetric pathology in SLE but further studies are required to characterize the subtle complexities of vitamin D's relationship with cytokine production and disease activity in these patients.